The Current State of Critical Limb Ischemia: A Systematic Review - Farber, Alik; Eberhardt, Robert T (JAMA surgery, 2016)
Chronic critical limb ischemia, marked by intractable lower extremity ischemic rest pain and tissue loss, is a highly morbid condition that leads to the loss of ambulation and decreased quality of life. It is associated with a high risk of limb loss and mortality and presents a significant economic burden to society. To review the current state of epidemiology, pathophysiology, diagnosis, and treatment of critical limb ischemia. An extensive literature search of the subject matter was conducted on material published in English between 1980 and 2016; both landmark and recently published articles were evaluated. Articles were reviewed if they included the terms critical limb ischemia, ischemic rest pain, gangrene, or extremity ulcers. Critical limb ischemia represents the end stage of peripheral arterial disease. Because peripheral arterial disease is most commonly caused by atherosclerosis, critical limb ischemia is heavily associated with smoking and diabetes. Revascularization is the cornerstone of therapy to prevent limb amputation, and both open vascular surgery and endovascular therapy play a key role in the treatment of patients with critical limb ischemia. However, few scientific data are available to identify the optimal revascularization strategy, which has led to a significant amount of variability and equipoise in the treatment of this condition. Medical therapy plays a significant role in optimizing coexistent cardiovascular risk factors and a limited role in improving limb outcomes in nonrevascularizable disease. Understanding critical limb ischemia and its treatment strategies is important for providing the best care for affected patients. Currently, ongoing randomized clinical trials in North America and the United Kingdom aim to provide data to support the best management of these patients.